SOSIALISASI PENGUATAN ETIKA PEMANFAATAN KECERDASAN BUATAN (AI FOR GOOD) BAGI SIVITAS AKADEMIKA FAKULTAS SAINS DAN TEKNOLOGI UIN SUMATERA UTARA - Khairul, Khairul; Razaq, Abdul; Irwan, Irwan; Hidayat, Rahmat; Pasaribu, Ryan Fahreza; Ritonga, Solahuddin Asri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The development of Artificial Intelligence (AI) technology has brought significant transformations in education, research, and academic governance. However, the use of AI without an ethical foundation has the potential to cause problems such as plagiarism, data privacy violations, algorithmic bias, and the degradation of academic integrity. This community service activity aims to increase the understanding and awareness of the academic community at the Faculty of Science and Technology, UIN North Sumatra, regarding the ethical principles of AI utilization within the AI for Good framework. The implementation methods include interactive outreach, contextual material delivery, case studies, and participatory discussions that emphasize the values of responsibility, transparency, accountability, and social benefits. This activity involved lecturers, educational staff, and students as active participants. The results of the activity showed an increase in participants' understanding of the risks and opportunities of AI use, as well as a commitment to integrating ethical principles into academic and research practices. This program is expected to be a strategic step in building an academic culture that is adaptive to technological developments, while remaining grounded in moral values, scientific integrity, and the vision of Islamic scholarship as rahmatan lil 'alamin. Keyword: Artificial Intelligence, Technology Ethics, Academic Integrity, Community Service Abstrak: Perkembangan teknologi Kecerdasan Buatan (Artificial Intelligence/AI) telah membawa transformasi signifikan dalam bidang pendidikan, riset, dan tata kelola akademik. Namun, pemanfaatan AI tanpa landasan etika berpotensi menimbulkan permasalahan seperti plagiarisme, pelanggaran privasi data, bias algoritmik, serta degradasi integritas akademik. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pemahaman dan kesadaran sivitas akademika Fakultas Sains dan Teknologi UIN Sumatera Utara mengenai prinsip-prinsip etika pemanfaatan AI dalam kerangka AI for Good. Metode pelaksanaan meliputi sosialisasi interaktif, penyampaian materi konseptual, studi kasus, serta diskusi partisipatif yang menekankan nilai tanggung jawab, transparansi, akuntabilitas, dan kebermanfaatan sosial. Kegiatan ini melibatkan dosen, tenaga kependidikan, dan mahasiswa sebagai peserta aktif. Hasil kegiatan menunjukkan adanya peningkatan pemahaman peserta terhadap risiko dan peluang penggunaan AI, serta komitmen untuk mengintegrasikan prinsip etika dalam praktik akademik dan penelitian. Program ini diharapkan menjadi langkah strategis dalam membangun budaya akademik yang adaptif terhadap perkembangan teknologi, namun tetap berlandaskan nilai-nilai moral, integritas ilmiah, dan visi keilmuan Islam yang rahmatan lil ‘alamin. Kata kunci: Kecerdasan Buatan, Etika Teknologi, Integritas Akademik, Pengabdian Masyarakat